2017
DOI: 10.2174/1389203717666160627074017
|View full text |Cite
|
Sign up to set email alerts
|

L-Arginine Modulates Glucose and Lipid Metabolism in Obesity and Diabetes

Abstract: Type 2 diabetes has become a global public health problem affecting approximately 380 million people throughout the world. It can cause many complications and lead to greater mortality. At present, there is no available medicine for effectively preventing diabetes. L-arginine, a functional amino acid, the precursor of nitric oxide, plays a crucial role in maintenance, reproduction, growth, anti-aging and immunity for animals. Growing clinical evidence indicates that dietary L-arginine supplementation can reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
82
2
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 103 publications
(90 citation statements)
references
References 0 publications
5
82
2
1
Order By: Relevance
“…Additionally, we found that arginine (ARG) and GLY content was fivefold higher in bovine colostrum than that in human colostrum. A recent study showed that ARG stimulates the growth and development of fetal brown adipocyte precursor cells by modulating protein turnover, and that l ‐ARG plays a crucial role in the maintenance of human immune function, as well as processes associated with human growth and anti‐aging . Additionally, GLY exhibits multiple functions related to metabolism, growth, immunity, and survival .…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, we found that arginine (ARG) and GLY content was fivefold higher in bovine colostrum than that in human colostrum. A recent study showed that ARG stimulates the growth and development of fetal brown adipocyte precursor cells by modulating protein turnover, and that l ‐ARG plays a crucial role in the maintenance of human immune function, as well as processes associated with human growth and anti‐aging . Additionally, GLY exhibits multiple functions related to metabolism, growth, immunity, and survival .…”
Section: Resultsmentioning
confidence: 99%
“…More research would be needed to relate short‐term changes of FA contents at rumen, blood plasma and mammary gland levels, so we are able to distinguish the role of ruminal microbiota and mammary and extramammary tissues . On the other hand, several genes that are involved in the regulation of lipid metabolism and the signalling pathways that regulate expression of those genes have been identified in humans and animals in recent years . However, further studies would allow a better understanding of the regulation of ruminant lipid metabolism at a molecular level …”
Section: Resultsmentioning
confidence: 99%
“…33,34 On the other hand, several genes that are involved in the regulation of lipid metabolism and the signalling pathways that regulate expression of those genes have been identified in humans and animals in recent years. [35][36][37] However, further studies would allow a better understanding of the regulation of ruminant lipid metabolism at a molecular level. 38…”
Section: Polyunsaturated Fatty Acidsmentioning
confidence: 99%
“…Derivatives of arginine include the urea cycle metabolites, arginine, citrulline, ornithine and methylarginines, including N‐monomethyl‐l‐arginine (NMMA), asymmetric dimethylarginine (ADMA) and symmetric dimethylarginine (SDMA). Interventions involving these metabolites may potentially delay or prevent T2D onset …”
Section: Introductionmentioning
confidence: 99%
“…Interventions involving these metabolites may potentially delay or prevent T2D onset. 2 The Prevención con Dieta Mediterránea (PREDIMED) trial was a large multicentre primary prevention trial in Spain that compared the effect of a Mediterranean diet with extra virgin olive oil (EVOO) or nuts with the effect of advising participants to adhere to a low-fat control diet. The previously reported finding was that a hazard ratio (HR) of 0.70 (95% confidence interval [CI] 0.54-0.92) for T2D incidence in the two Mediterranean-diet groups combined versus the control group was observed 3 ; however, the biological mechanisms by which a Mediterranean diet can reduce T2D risk, and whether a Mediterranean diet may offset an unfavourable metabolite profile, remain unsettled.…”
Section: Introductionmentioning
confidence: 99%